Charge Photogeneration for a Series of Thiazolo‐Thiazole Donor Polymers Blended with the Fullerene Electron Acceptors PCBM and ICBA. (6th February 2013) - Shoaee, Safa; Subramaniyan, Selvam; Xin, Hao; Keiderling, Chaz; Tuladhar, Pabitra Shakya; Jamieson, Fiona; Jenekhe, Samson A.; Durrant, James R.
Abstract Photoinduced charge separation in bulk heterojunction solar cells is studied using a series of thiazolo‐thiazole donor polymers that differ in their side groups (and bridging atoms) blended with two acceptor fullerenes, phenyl‐C71‐butyric acid methyl ester (PC71BM) and a fullerene indene‐C60 bisadduct (ICBA). Transient absorption spectroscopy is used to determine the yields and lifetimes of photogenerated charge carriers, complimented by cyclic voltammetry studies of materials energetics, wide angle X‐ray diffraction and transmission electron microscopy studies of neat and blend film crystallinity and photoluminescence quenching studies of polymer/fullerene phase segregation, and the correlation of these measurements with device photocurrents. Good correlation between the initial polaron yield and the energetic driving force driving charge separation, ΔECS is observed. All blend films exhibit a power law transient absorption decay phase assigned to non‐geminate recombination of dissociated charges; the amplitude of this power law decay phase shows excellent correlation with photocurrent density in the devices. Furthermore, for films of one (relatively amorphous) donor polymer blended with ICBA, we observe an additional 100 ns geminate recombination phase. The implications of the observations reported are discussed in terms of the role of materials' crystallinity in influencing charge dissociation in such devices, and thus materials design requirements for efficient solar cell function.